Exploring the cultural dimensions of the right to the highest attainable standard of health - Donders, Yvonne (My University, 2015)
The right to enjoying the highest attainable standard of health is incorporated in many international and regional human rights instruments. This right contains both freedoms and entitlements, including the freedom to control one's own health and body and the right to an accessible system of health care, goods and services. Both aspects of the right to health - freedoms and entitlements - have important cultural dimensions. The UN Committee on Economic, Social and Cultural Rights has for instance stated that the right to health implies that health facilities, goods and services must be culturally appropriate, in other words respectful of the culture of individuals and communities. At the same time, it should be noted that culture and health may have a problematic relationship. Cultural patterns, attitudes or stereotypes may severely limit the health freedoms of people or may prevent certain people from accessing health care. Furthermore, there are some cultural or traditional practices that are condoned but that are very harmful to people's health. It seems that international human rights law demands respect for the cultural dimensions of the right to health, while at the same time requiring protection of the right to health against negative aspects of cultures. How does this work out in practice? What does the concept of "culturally appropriate" health goods and services mean at the national level? Who decides on what is or is not culturally appropriate? How have international supervisory bodies elaborated on the freedoms and entitlements of the right to health and the obligations for States Parties to the treaties in relation to the cultural dimensions of the right to health? This article analyses several treaty provisions and the interpretation of these provisions by the treaty monitoring bodies. Apart from several UN treaties, several regional treaties in Africa are dealt with, notably the African Charter on Human and Peoples' Rights. The article concludes that various cultural dimensions of the right to health are recognised and elaborated upon in recommendations by treaty monitoring bodies both at UN and African level. These bodies have endorsed the idea that health facilities, goods and services must be respectful of the culture of individuals, peoples and communities. At the same time, the right to health should be protected against the negative impact that cultural values, patterns or practices may have, such as on access to health goods and services and on the health of people as such. The latter issue has received most attention at the UN as well as at African level, and there appears to be a clear consensus on several practices that are considered harmful. It is also realised, however, that the identification of a certain practice as harmful by an international body, even if agreed to by the State Party, is not sufficient to eradicate it. Cultural communities are crucial in promoting social and behavioural changes that may be needed to eradicate harmful practices. It is therefore important to involve the cultural communities concerned in the drafting, implementation and evaluation of health laws and policies. This could be more emphasised by the monitoring bodies. The involvement of the cultural community is also crucial to respecting and promoting the more positive cultural dimensions of the right to health. By consulting the cultural communities and individuals concerned, States can implement the right to the enjoyment of the highest attainable standard of health in a culturally sensitive, appropriate and responsible way.
Keywords: Culture; Cultural diversity; Health; Human rights; Right to health; Traditional practices